Distinct cellular pathways for resistance to urea stress and hypertonic stress - Lee, Sang Do (American Physiological Society, 2011)
During antidiuresis with elevated vasopressin, urea accumulates in the renal medulla to very high concentrations, imposing considerable cellular stress. How local cells cope with urea stress is relevant to the whole kidney because the renal medulla is the major site of residence for the renal stem cells. Previous studies showed that renal cells were incapable of preconditioning in moderate urea concentrations to enhance resistance to urea stress. Instead, preconditioning in moderately high salinity (moderate hypertonicity) has been shown to promote resistance to urea stress due to the induction of the molecular chaperone heat shock protein 70 (Hsp70), which is mediated by the transcription factor tonicity-responsive enhancer binding protein (TonEBP). Here we report that cell lines derived from the kidney and fibroblasts display enhanced resistance to urea stress after pretreatment in moderate, nonstressful concentrations of urea. Using TonEBP knockdown and immunoblot analyses, we demonstrate that TonEBP and Hsp70 are dispensable for the increased resistance to urea stress. These data suggest that cells in the renal medulla are capable of overcoming urea stress by activating distinct cellular pathways.